2000
DOI: 10.1071/bt99066
|View full text |Cite
|
Sign up to set email alerts
|

Allometric relationships and community biomass estimates for some dominant eucalypts in Central Queensland woodlands

Abstract: Allometric equations are presented relating stem circumference to branch, leaf, trunk, bark, total above-ground and lignotuber biomass for Eucalyptus crebra F.Muell. (woodland trees), E. melanophloia Sol. Ex Gaerth. (both woodland and regrowth community trees) and E. populnea F.Muell. (woodland trees). There were no significant differences (P > 0.05) between the slopes of individual lognormal regression lines plotting stem circumference against total above-ground biomass for E. crebra, E. melanophloia and E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(41 citation statements)
references
References 12 publications
0
40
0
1
Order By: Relevance
“…Since the main woody vegetation was open forest and woodland, forest and woodland will be described as simply woodland in following sections for simplicity. Although Taniguchi et al (2002a) reported that the average woodland biomass in this research area was 16 Mg ha À1 , which is quite low, the comparison among the aboveground biomass shown in Table 3, that of O' Grady et al (2000) and that of Burrows et al (2000) revealed that the forest biomasses among arid areas with 211 mm precipitation (this report), semiarid areas with 450 mm precipitation (Burrows et al, 2000) and temporal area with 1200 mm precipitation (O'Grady et al, 2000) did not differ significantly at the same SBA level. The area with good environmental conditions had high biomass comparable to that of the other climatic area.…”
Section: Forest and Woodland Measurementmentioning
confidence: 85%
See 1 more Smart Citation
“…Since the main woody vegetation was open forest and woodland, forest and woodland will be described as simply woodland in following sections for simplicity. Although Taniguchi et al (2002a) reported that the average woodland biomass in this research area was 16 Mg ha À1 , which is quite low, the comparison among the aboveground biomass shown in Table 3, that of O' Grady et al (2000) and that of Burrows et al (2000) revealed that the forest biomasses among arid areas with 211 mm precipitation (this report), semiarid areas with 450 mm precipitation (Burrows et al, 2000) and temporal area with 1200 mm precipitation (O'Grady et al, 2000) did not differ significantly at the same SBA level. The area with good environmental conditions had high biomass comparable to that of the other climatic area.…”
Section: Forest and Woodland Measurementmentioning
confidence: 85%
“…In the case of the woodland biomass calculation with allometric equations in E. camaldulensis woodland, the independent variable of the allometric equation E(I) was DBH 2 Â H, but the estimation accuracy of equation E(2) became better than that of equations E(10) or E(11). In other climatic areas of Australia, O'Grady et al (2000) and Burrows et al (2000) adopted SBA as their independent variable for biomass estimation equations, although they named the forest biomass estimation equations as Stand Allometric Equations. Their research areas were the temporal eucalyptus forest with 1200 mm annual precipitation and the semiarid eucalyptus forest with 450 mm annual precipitation.…”
Section: Stand Basal Areamentioning
confidence: 99%
“…We used a modified transect method for recording tree locations within a 0.05 ha (50 Â 10 m) plot (Stohlgren et al, 1995;Back et al, 1997;Back et al, 1999;Burrows et al, 2000;Burrows et al, 2002;Crowley et al, 2009), that ensures both accuracy and repeatability, and is suited to estimating high stem densities in rainforest patches on steep slopes. Sampling was conducted about the central line (x-axis) of each plot, which was oriented along a compass bearing (Fig.…”
Section: Tree Measurement Plot Methodsmentioning
confidence: 99%
“…However, previous studies show that generalized models do not accurately predict aboveground biomass (Maraseni et al 2005;Litton et al 2006;Litton and Kauffman 2008). Major sources of uncertainties include (i) differences in site indices, including soil and climatic conditions, unquantified diameter and height ranges (Specht and West 2003), narrow ranges of diameter and height (Burrows et al 2000), and (iv) differences in age classes and tree density (Chen et al 1998;Lin et al 2001). Generalized models based on pooled data from different sites can be used to estimate C stocks of species at different sites as long as trees are of the same age and are sharing the same diameter and H ranges, and are growing in a location with similar site indices.…”
Section: Allometric Functions For Estimation Of Carbon In Abovegroundmentioning
confidence: 94%